Advertisements

Question 4: Factorize 4 x 2 – 36 x + 27

Question 4: Factorize 12x 2 – 36 x + 27

Factorizing an expression —

Solution:

 

Given expression is

12 x^{2}-36x+27

=3(4x^{2}-12x+9)

We convert  (4x^{2}-12x+9) part of this expression to  (a)^{2}-2(a)(b)+ (b)^{2}= (a-b)^{2}   form;

=3[(2x)^{2}-2(2x)(3)+(3^{2})]

=3[(2x-3)^{2}]

So here, 3 is factor and (2x-3) is two times factor of the given expression.

 

This so because as per formula in [(2x)^{2}-2(2x)(3)+(3^{2})];

2x stands for a

3 stands for b

and

(2x-3) stands for (a-b)

 

 


 

 

 

 

  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  

You may submit a MCQ or maths problem with solution tips here in the comment box below! If you could not solve anyone, you may submit a MCQ or maths problem without solution as well. We will try our level best to solve it for you!

Your email address will not be published.

You may use these <abbr title="HyperText Markup Language">HTML</abbr> tags and attributes: <a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>

All original content on these pages is fingerprinted and certified by Digiprove
Insert math as
Block
Inline
Additional settings
Formula color
Text color
#333333
Type math using LaTeX
Preview
\({}\)
Nothing to preview
Insert